2023
DOI: 10.1002/anie.202312721
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective High‐Throughput Assay Showcased for the Identification of (R)‐ as well as (S)‐Selective Unspecific Peroxygenases for C−H Oxidation

Alexander Swoboda,
Lukas Johannes Pfeifenberger,
Zerina Duhović
et al.

Abstract: Identifying (bio)catalysts displaying high enantio/stereoselectivity is a fundamental prerequisite for the advancement of asymmetric catalysis. Here, a high‐throughput, stereoselective screening assay is reported giving information on enantioselectivity, stereopreference and activity showcased for peroxygenase catalyzed hydroxylation. The assay is based on analyzing spectrophotometrically the simultaneous formation of NAD(P)H from the alcohol dehydrogenase catalyzed enantioselective oxidation of the sec‐alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…16 To further investigate the peroxygenase-catalyzed allylic hydroxylation and overoxidation, a panel of 44 UPOs from Aminoverse was screened (Figure 2A). 23 These UPOs were recently discovered and produced in Pichia pastoris. 23 Very diverse results were obtained.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 To further investigate the peroxygenase-catalyzed allylic hydroxylation and overoxidation, a panel of 44 UPOs from Aminoverse was screened (Figure 2A). 23 These UPOs were recently discovered and produced in Pichia pastoris. 23 Very diverse results were obtained.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Interestingly, MorUPO was also recently reported to provide racemic 1-phenylethanol from ethylbenzene. 23 Next, a panel of ADHs was screened using racemic 4, including in-house enzymes LbADH and LkADH, and the C� O-reduction kit provided by JM (Figure 3). Almost all ADHs screened achieved >90% conversion, accepting both enantiomers of 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, based on variant M4, variant M5 (T125A/A129V/A247H/T244A/F243G) was obtained by mutating F to G at position 243, which further enhanced the enantiomeric excess to 84% ee ( S ) (Figure C and Table S5). To our knowledge, variant M5 represents the highest ( S )-enantioselectivity for UPOs catalyzed benzylic hydroxylation of ethylbenzene, surpassing all the reported natural UPOs or their variants [ Gdi UPO-II: 61% ee ( S ), Cab UPO-V: 20% ee ( S ), Aae UPO variant d28: 32% ee ( S ), and Abr UPO: 20% ee ( S )]. ,, …”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, variant M5 represents the highest (S)enantioselectivity for UPOs catalyzed benzylic hydroxylation of ethylbenzene, surpassing all the reported natural UPOs or their variants [GdiUPO-II: 61% ee (S), CabUPO-V: 20% ee (S), AaeUPO variant d28: 32% ee (S), and AbrUPO: 20% ee (S)]. 15,33,34 Subsequently, the two CmaUPO variants M2a and M5 were extracellularly expressed in P. pastoris X33, and the enzyme was then purified and employed for kinetic study. It was found that both variants exhibited higher catalytic efficiency (k cat /K m ) compared to that of WT CmaUPO (Table 2 and Figure S15).…”
Section: Engineering Cmaupo For Enantioselectivity Controlmentioning
confidence: 99%